An Empirical Study on Employee Job Satisfaction and Job Performance in Private Sector Banks - Sasmita Mohanty, Bibhuti B.Pradhan, Ashish Mohanty (International Journal of Advanced Science and Technology, 2020)
Nowdays organisations rely heavily on their human resources for optimal employees’ productivity which by and large will result in the overall efficiency of the organisations. Thus, the need of the hour for any organisation is to ensure employee job satisfaction (EJS). In this regard, the present study is intended to study the concepts of employee job satisfaction and employee job performance (EJP) and to assess employees’ job satisfaction influence on their job performance in private sector banks in Bhubaneswar, Odisha. Job Satisfaction Survey by Spector, P.E (1997) and Employee Job Performance Scale by Na-Nan et al., (2018) were distributed to the respondents through a purposive sampling technique. The data collected is analysed using SPSS 20.0. Statiscical tools such as Descriptived Analysis, Correlation Analysis and Multiple Regression Analysis were carried out to test the veracity of the research. The results of the analysis revealed that all the dimensiosn of job satisfaction are significant and positvely correlated and employee job satisfaction influences employee job performance to a larger extent. Based on the findings, suggestions/recommdations were given to the management to provide an impetus in the field of organisational behavoiur and human resources manag